Fascinating Nutritional, Prophylactic, Therapeutic and Socio-Economic Reconcile Attributable to Drum Stick Tree (Moringa Oleifera Lam.) (Global Journal of Medical Research, 2014)
Different parts of this M. oilbera ( Drum Stick Tree ) contain a profile of important minerals, and are a good source of vitamins, β-carotene, amino acids and various phenolics. The Moringa plant provides a rich and rare combination of zeatin, quercetin, β-sitosterol, caffeoylquinic acid and kaempferol. In addition to its compelling water purifying powers and high nutritional value. Various parts of this plant such as the leaves, roots, seed, bark, fruit, flowers and immature pods act as cardiac and circulatory stimulants, possess antitumor, antipyretic, antiepileptic, antiinflammatory, antiulcer, antispasmodic, diuretic, antihypertensive, cholesterol lowering, antioxidant, antidiabetic, hepatoprotective, antibacterial and antifungal activities, and are being employed for the treatment of different ailments in the indigenous system of medicine, particularly in South Asia.
Keywords: ROS; antioxidants; Free radicals; SOD; GTH; oxidative stress; pathogenesis; CVD; diabetes; water purification; biodiesel; quercetin-3-O-#x3B2; -d-glucoside